Targeting the Wnt/β-catenin pathway and epithelial-mesenchymal transition in gastric cancer: mechanisms, therapeutic strategies, and clinical challenges - Shi, Ruixin; Cao, Zhenwen; Li, Jie; Ji, Ru; Guo, Zhijuan (Frontiers in Oncology, 2025)
Gastric cancer (GC) remains the foremost contributor to global cancer mortality, largely attributable to metastatic dissemination and therapeutic refractoriness. Emerging data implicate the Wnt/β-catenin signaling cascade as a pivotal regulator of epithelial-mesenchymal plasticity, stemness acquisition, and multidrug tolerance in GC. This review delineates the molecular landscape of Wnt/β-catenin aberrations, encompassing genomic perturbations (NAT10, SMC4), non-coding RNA circuitry (LINC00665, circ0000670), and (epigenetic reprogramming (e.g., miR-33b hypermethylation). Mechanistically, these alterations cooperate with EMT drivers to potentiate metastatic outgrowth and therapeutic evasion. Of particular translational significance are emerging interventions targeting this axis: phytochemicals (Rutin, ginsenoside Rg3) with dual Wnt-CSC inhibitory activity, CRISPR-edited epigenetic modulators (TET1/FOXO4), and immune checkpoint blockade-Wnt inhibitor synergism. Notwithstanding preclinical success, clinical implementation faces two critical bottlenecks—pathway pleiotropy and biomarker paucity. To bridge this gap, we propose a precision oncology framework leveraging multi-omics-guided patient stratification, potentially reshaping GC therapeutic paradigms.